2014
DOI: 10.1016/j.joca.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Single cell sorting identifies progenitor cell population from full thickness bovine articular cartilage

Abstract: Objective To date, no approved clinical intervention successfully prevents the progressive degradation of injured articular cartilage that leads to osteoarthritis (OA). Stem/progenitor cell populations within tissues of diarthrodial joint have shown their therapeutic potential in treating OA. However, this potential has not been fully realized due in part to the heterogeneity of these subpopulations. Characterization of clonal populations derived from a single cell may help identify more homogenous stem/progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 31 publications
2
45
0
Order By: Relevance
“…CCL5 has been reported to be involved also in MSCs recruitment [54], and thus it is considered attractive for regenerative therapies. As already reported [85], high levels of CXCL12/SDF-1α in chondro-progenitor secretome may indicate their ability to mobilize other endogenous progenitor cells within injured articular joints and recruit immune cells in order to help in mediating tissue repair.…”
Section: Discussionsupporting
confidence: 56%
“…CCL5 has been reported to be involved also in MSCs recruitment [54], and thus it is considered attractive for regenerative therapies. As already reported [85], high levels of CXCL12/SDF-1α in chondro-progenitor secretome may indicate their ability to mobilize other endogenous progenitor cells within injured articular joints and recruit immune cells in order to help in mediating tissue repair.…”
Section: Discussionsupporting
confidence: 56%
“…The digestion media was then centrifuged (300 G for 10 mins) and resuspended, cells were seeded into multiple 35 mm dishes. To determine if phagocytic cells were enriched in the superficial zone, chondrocytes from the upper 1/3 cartilage were separated from the bottom 2/3 prior to cell isolation using a customized fixture [9]. All cells were allowed to adapt to culture conditions for at least two days before measuring phagocytic activities.…”
Section: Methodsmentioning
confidence: 99%
“…The overall pattern of CPC gene expression revealed by microarray analysis is more akin to synovial fibroblasts and mesenchymal stem cells than chondrocytes [8]. Unlike pluripotent MSCs, CPCs are limited in their ability to form different tissues; however, as their name implies, CPCs reliably generate hyaline cartilage under chondrogenic conditions [9]. …”
Section: Introductionmentioning
confidence: 99%
“…We subjected fresh intact human and animal articular cartilage specimens, maintained in environments simulating in vivo conditions, to a range of acute impacts, repetitive loadings, and direct mechanical injuries. Investigations using these explants have revealed that injurious mechanical loads stimulate biologic responses that cause progressive cell death and activate chondrocyte progenitor cells (CPCs) (Table S1) …”
Section: Class I: Explant and Whole Joint Modelsmentioning
confidence: 99%